105 The use of a high fidelity simulator to facilitate coaching in the implementation and manual titration of non-invasive ventilation (NIV) during a cardiorespiratory sleep study in a controlled and safe environment. (30th November 2020) - Simpson, Gabrielle; Davies, Matthew
Abstract : Introduction: The aim of this programme was to pilot a simulation to help develop practitioners' confidence in decision making and implementation of NIV in set scenarios whilst having the support of senior practitioners' in debrief. Methods: Using a high fidelity simulator candidates were exposed to an immersive simulation which accurately obtained physiological data within the sleep recording system as expected in clinical practice. The level of immersion was hugely increased with the utilisation of Simulation Technicians' knowledge in the capabilities of the high fidelity manikin, together with subject matters and experts enabling an authentic environment. Trialling this over a 6 month period was required to create complex paediatric respiratory sleep patterns which are commonly seen in clinical practice when CYP are treated with NIV, such as apnoeas, hypopnoeas and changes in gas exchange parameters including oxygen saturations and carbon dioxide measurements. Two half day sessions were built around 2–3 scenarios allowing for substantial debrief to identify any human factors or gaps in clinical knowledge. Further, a pre and post confidence survey was conducted. Results: As previously discussed, a pre and post confidence survey was conducted. The questions were focused and specific to match the learning objectives and the needs identified in the initial educational needs analysis. The overall increase in confidence averaged 2.1 and all candidates discussed the direct impact this would have on their clinical practice. Discussion: The use of simulation for paediatric sleep studies with manual titration of ventilation has not been undertaken before in the UK. The pilot study identified the need to progressively increase the complexities of each scenario, whereby candidates feel comfortable to make appropriate clinical decisions in a safe controlled environment. Furthermore, it highlighted a necessity for the manufacturers to develop instant paediatric respiratory pattern and gas exchange alteration packages within the manikin software.